The mechanisms of glycolipid metabolism disorder on vascular injury in type 2 diabetes - Chen, Xiatian; Shi, Chengzhen; Wang, Yin; Yu, Hua; Zhang, Yu; Zhang, Jiaxuan; Li, Peifeng; Gao, Jinning (Frontiers in Physiology, 2022)
Patients with diabetes have severe vascular complications, such as diabetic nephropathy, diabetic retinopathy, cardiovascular disease, and neuropathy. Devastating vascular complications lead to increased mortality, blindness, kidney failure, and decreased overall quality of life in people with type 2 diabetes (T2D). Glycolipid metabolism disorder plays a vital role in the vascular complications of T2D. However, the specific mechanism of action remains to be elucidated. In T2D patients, vascular damage begins to develop before insulin resistance and clinical diagnosis. Endothelial dysregulation is a significant cause of vascular complications and the early event of vascular injury. Hyperglycemia and hyperlipidemia can trigger inflammation and oxidative stress, which impair endothelial function. Furthermore, during the pathogenesis of T2D, epigenetic modifications are aberrant and activate various biological processes, resulting in endothelial dysregulation. In the present review, we provide an overview and discussion of the roles of hyperglycemia- and hyperlipidemia-induced endothelial dysfunction, inflammatory response, oxidative stress, and epigenetic modification in the pathogenesis of T2D. Understanding the connections of glucotoxicity and lipotoxicity with vascular injury may reveal a novel potential therapeutic target for diabetic vascular complications.